2007
DOI: 10.1177/0269215506071252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of home-based sensory and motor amplitude electrical stimulation on arm dysfunction in chronic stroke

Abstract: Subjects with chronic stroke can experience impairment and functional improvements following a home-based programme of motor and sensory amplitude electrical stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 29 publications
3
40
1
1
Order By: Relevance
“…[3][4][5] Although both high-and low-NMES groups showed better treatment effects than did the control group, our results did not demonstrate a significant difference between the 2 NMES groups. Increasing the stimulation dose of NMES did not lead to greater improvement.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…[3][4][5] Although both high-and low-NMES groups showed better treatment effects than did the control group, our results did not demonstrate a significant difference between the 2 NMES groups. Increasing the stimulation dose of NMES did not lead to greater improvement.…”
Section: Discussioncontrasting
confidence: 74%
“…1,2 Past studies have shown that neuromuscular electrical stimulation (NMES) not only facilitates sensorimotor function recovery [3][4][5] but also produces brain plasticity. 6,7 Among these studies, the treatment intensity and duration have varied widely (30 minutes to 6 hours per day, for a period of 2 to 12 weeks).…”
mentioning
confidence: 99%
“…204 Although many small studies have found that mental imagery in concert with physical practice improves motor outcomes, individual differences in lesion location may influence the utility of mental imagery. 154,251,252 There is strong evidence for the efficacy of electric stimulation for individuals with chronic stroke, 151,152,154,155,189,253,254 yet the effects of electric stimulation on the maintenance of functional gains are variable, 151 and although the selection of included articles was limited, a recent meta-analysis failed to find an advantage of electric stimulation to the wrist and fingers over usual care. 149 For the LE, Cozean et al 255 determined that FES combined with biofeedback produced better results than standard PT, FES, or biofeedback alone.…”
Section: Activities and Participationmentioning
confidence: 99%
“…When this recovery is enabled, hebbian learning might re-establish the neuronal connections, through unmasking of synapse connections or sprouting of new synapses (Sullivan & Hedman, 2008), both of which could be related to hebbian learning. This involvement of hebbian learning could then explain the effect induced by stimulation also at the lower frequency of 25 Hz (Sullivan & Hedman, 2007). Indeed, in this later phase of recovery, somatosensory stimulation protocols might be even more effective in inducing recovery, as they induce excitation and increase synaptic efficacy (see above).…”
Section: Rts Induced Behavioral Effects On Motor Control and Possiblementioning
confidence: 95%
“…Yet, sensory stimulation of the palm at 25 Hz reduced spasticity measured through the Ashworth scale by 10 % (Sullivan & Hedman, 2007). This might indicate that treatment of spasticity demands stronger stimulation parameters than those applied in some somatosensory stimulation protocols.…”
Section: Rts Induced Behavioral Effects On Motor Control and Possiblementioning
confidence: 97%